2003
DOI: 10.1093/sw/48.2.187
|View full text |Cite
|
Sign up to set email alerts
|

Parents with Serious and Persistent Mental Illness: Issues in Assessment and Services

Abstract: Parents who have serious and persistent mental illness are often overlooked in social work and mental health journals. Furthermore, mentally ill parents typically are viewed from a pathology perspective that fails to address their desire to be competent parents. This article reviews the literature on mentally ill parents and addresses conceptual issues in assessment and services. The author critiques methods of assessment and recommends more appropriate and comprehensive assessment protocols. Model programs ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
64
0
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(66 citation statements)
references
References 31 publications
0
64
0
2
Order By: Relevance
“…Burton, Jr. (1990) also found that 20 states statutorily remove children from the custody of mentally ill parents because of stigma, and a lack of social support and employment. Caseworkers and the courts frequently argue that parents diagnosed with mental illness are incapable of assuming caregiving roles (Ackerson, 2003), and their children are removed from their custody as a result (Burton, Jr., 1990). Caseworkers, child welfare professionals and the courts may also assume that caregiving is devalued by parents with mental illness (Ackerson, 2003), although study findings indicate otherwise (e.g., Mowbray, Oyserman, & Ross, 1995).…”
Section: Mental Healthmentioning
confidence: 99%
“…Burton, Jr. (1990) also found that 20 states statutorily remove children from the custody of mentally ill parents because of stigma, and a lack of social support and employment. Caseworkers and the courts frequently argue that parents diagnosed with mental illness are incapable of assuming caregiving roles (Ackerson, 2003), and their children are removed from their custody as a result (Burton, Jr., 1990). Caseworkers, child welfare professionals and the courts may also assume that caregiving is devalued by parents with mental illness (Ackerson, 2003), although study findings indicate otherwise (e.g., Mowbray, Oyserman, & Ross, 1995).…”
Section: Mental Healthmentioning
confidence: 99%
“…The prevalence of each of the risk factors is higher in this sample than in the general population. Nationally, 2% of children have an incarcerated parent (Johnson & Waldfogel, 2004), the poverty rate in the United States is approximately 13% (Corcoran & Chaudry, 1997), approximately 6% of children have a parent addicted to substances (Grant, 2000) and mentally ill parents are just as likely as those who are not mentally ill to parent at least one child (Ackerson, 2003). In the current sample 13% of children have a mentally ill parent, 11 % have a parent that uses substances, 17% have an incarcerated parent, and 70% live in poverty.…”
Section: Chapter V Discussionmentioning
confidence: 99%
“…An unexpected consequence of the community mental health revolution is that more people struggling with mental illness are raising children. Research indicates that women with mental illness marry and have children at the same rate as other women, but have higher separation and divorce rates (Ackerson, 2003) Craig (2004) stated that mothers with mental illness fall into two categories with the first category being comprised of those women who are mentally ill (Le.…”
Section: A Multiple Risk Modelmentioning
confidence: 99%
“…Mentally ill parents typically are viewed from a pathology perspective that fails to address their desire to be competent parents (Ackerson, 2003 (Ackerson, 2003). Before deinstitutionalization many of these individuals resided in state hospitals and may have been less likely to marry or have children.…”
Section: Parental Mental Illness and Emotional Problemsmentioning
confidence: 99%
“…Some have expressed concerns regarding child protection social workers' inability to effectively treat clients with mental illness and the lack of clear objectives for improving parenting and role definition for mental health providers whose clients are also in the child protection system (Ackerson, 2003;Raske, 1997). Due to many more mentally ill persons living in the community instead of mental health institutions, child protection social workers and mental health providers may be dealing with many rT\0re individuals who are mentally ill and parents.…”
Section: Level Of Family and Community Supportmentioning
confidence: 99%